Obstetric outcomes for twins from different conception methods – A multicenter cross‐sectional study from China. (11th March 2021) - Jiang, Fang; Gao, Jinsong; He, Jing; Tang, Yabing; Cao, Yinli; Wang, Xietong; Liu, Xiaowei; Wang, Tianyun; Liu, Xinghui; Sun, Jingxia; Zhong, Mei; Liu, Xiaohong; et al.
Abstract: Introduction: The effects of assisted reproductive technology on the outcomes of twin pregnancies are controversial. Therefore, the purpose of this study was to compare the maternal and perinatal outcomes of twin pregnancies conceived spontaneously and those conceived by assisted reproductive technology. Material and methods: This was a cross‐sectional study performed at Peking Union Medical College Hospital (PUMCH). Data on twin pregnancies (conceived spontaneously and by in vitro fertilization [IVF]/intracytoplasmic sperm injection [ICSI]) were obtained from the National Birth Registry of China for the period between 1 October 2016, and 30 September 2017. The primary obstetric outcomes were compared between twin pregnancies conceived by different methods. Logistic regression analysis with 95% confidence intervals (95% CI) was used for the multivariate analysis. Results: A total of 3270 twin pregnancies (2003 and 1209 conceived spontaneously and by IVF/ICSI, respectively) were identified. The proportion of twin pregnancies among all pregnancies was 3.4% (3332/97 278). Multiple regression analysis indicated that the incidences of gestational diabetes mellitus (adjusted odds ratio [AOR] = 1.42, 95% CI 1.10–1.83, p  = 0.007), preterm premature rupture of membranes (AOR = 1.65, 95% CI 1.21–2.25, p  = 0.002), placenta accreta spectrum (AOR = 2.12, 95% CI 1.42–3.17, p  < 0.001) and postpartum hemorrhage (AOR = 1.38, 95% CI 1.02–1.86, p  = 0.037) were significantly higher in the IVF/ICSI group than in the natural pregnancy group. Multivariate analysis also revealed that conception mode was not an independent risk factor for neonate outcomes. Conclusions: In twin pregnancies, IVF/ICSI is independently associated with multiple maternal complications, including gestational diabetes mellitus, preterm premature rupture of membranes and placenta accreta spectrum compared with spontaneous conception, although potential residual confounders due to indications for assisted reproductive technology exist.